Pitahaya (Hylocereus spp.): Culture, physicochemical characteristics, nutritional composition, and bioactive compounds - Verona-Ruiz, Anggie (2020)
The Pitahaya, commonly known as "dragon fruit", is a fruit originating in Central America and the Peruvian jungle whose fruit can be of different colors such as yellow, purple, red and white. This fruit has a high nutritional value, highlighting the content of ascorbic acid that is between 4-25 mg / 100g depending on its species, with the highest value being the red species. Pitahaya is a fruit with a high antioxidant capacity, even superior to that of other cacti, such as prickly pear. It presents bioactive compounds such as betalains; that favor stress-related disorders and have anti-inflammatory effects, it also has betanins and betacyanins; they are a source of natural dye. This review work aimed to collect information on the studies carried out on the Pitahaya related to its cultivation, physicochemical characteristics, nutritional composition, and bioactive compounds, for their health benefits, such as; avoid premature aging, reduce blood pressure levels and alleviate stomach and intestinal problems, and the consumption of pitahaya is recommended to counteract diseases such as diabetes and colon cancer.